Water requirement and water use efficiency of Sorghum and its irrigation planning under limited water resources in arid and semi arid regions of India - SAMUI, R. P.; JOHN, GRACY; PILLAI , M. P. S.; RANSURE, S. P. (MAUSAM, 2008)
Water requirement and water use efficiency of sorghum was studied at Akola, Parbhani, Rahuri and Coimbatore. The study enables to understand the consumptive water demand of sorghum and water use efficiency in relation to yield. The results can be used for efficient management of both rainfall and limited water resources available for sorghum production. Seasonal Evapotranspiration (ET) losses were studied for non- irrigated kharif sorghum at Akola and Parbhani and for Rahuri and Coimbatore seasonal ET losses were studied for rabi sorghum for well distributed normal and deficit rainfall years. In the normal rainfall years ET losses were more compared to deficit rainfall years. However, water use efficiency was found higher during deficit rainfall years than normal rainfall years. The seasonal ET- yield relationship was found positively correlated but insignificant for Akola, Parbhani, Rahuri and significant for Coimbatore (5% level). At Akola and Parbhani optimum yields were observed for seasonal ET of around 486 mm and 470 mm respectively. At Coimbatore maximum yield was observed for seasonal ET of 416 mm whereas at Rahuri yield was maximum when ET loss was about 475 mm. Water Use Efficiency (WUE) ranged from 6.3 to 12.2 mm for kharif season and 5.5 to 10.1 mm for rabi sorghum. Crop coefficient Kc was found negligible during early growth stages and reached peak during flowering stage and declined subsequently during maturity to harvesting stage. The study revealed that during deficit rainfall years life saving irrigation need to be applied for all stations under consideration. If limited irrigation is available irrigations at vegetative stage (25-35 days after sowing) and at boot- flowering stage (55-65 days after sowing) be given. The boot stage is found to be the most critical stage and if only one irrigation is available, it may be given at this stage. Water stress at this stage is found to cause reduction in yield by 35 to 40%.